Where are the fastest master butterfly swimmers competing in the FINA World Masters Championships from? - Weiss, K.; Seffrin, A.; Andrade, M. S.; Ahmad, W.; Forte, P.; Moreitz, S.; Stanula, A.; Cuk, I.; Nikolaidis, P. T.; Knechtle, B. (EXCLI Journal, 2023)
While the butterfly stroke has received considerable attention in sports science, the origin of the fastest master butterfly swimmers remains unknown. The present study investigated which geographical locations produce the top-performing master butterfly swimmers within their age groups and gender. A total of 26,512 master butterfly swimmers (11,288 women and 15,224 men) competed in 50 m, 100 m and 200 m races in World Masters Championships held between 1986 and 2019. From each swimmer, the year of competition, first name, last name, age group and distance were recorded. Descriptive data were presented using mean, standard deviation, maximum and minimum values, and/or confidence intervals. The top 10 race times for master butterfly swimming and gender were identified for descriptive purposes. Nationalities were then grouped into six categories: the top five nationalities with the most appearances in the top 10 fastest times in butterfly swimming by distance each year and one group consisting of all other nationalities. In the event of a tie, the nationality with the most participants overall was selected. Generalized linear models (GLMs) with a gamma probability distribution and log link function were used to assess the effect of age groups and gender on swimming time. In summary, Germany had the fastest women butterfly master swimmers across all distances, while the USA had the fastest men butterfly master swimmers for all distances. Men covered all distances faster than women and younger swimmers were quicker than older swimmers. The results of this study can be utilized to determine the countries that produce the most successful master butterfly swimmers, providing a foundation for further research to explore the factors that lead to their success.